Studies in the Islamic built environment - Omer, Spahic (IIUM Press, 2013)
In September 2000, when I joined the Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, from the Kulliyyah of Islamic Revealed Knowledge and Human Sciences, to teach some courses related to Islamic worldview, history and civilization, as well as to review and develop the syllabuses of some other courses, the first thing that struck me was the overwhelming enthusiasm of the Kulliyyah to Islamize its curriculum and introduce as many Islamic ingredients as possible in it. The next thing that I almost immediately had to come to terms with, however, was the fact that works on Islamic built environment, which is one of the core interests of the Kulliyyah, are far from satisfactory, making the process of the intended Islamization all the more challenging and easier said than done. Regrettably, most of such works have been produced by authors - Muslims and non-Muslims alike – who fell short of perceiving, partly or completely, that the tawhidic (God’s Oneness) spirit of Islam – a comprehensive way of life - was the sole force which furnished Islamic built environment with both its essence and identity, relegating the indigenous geographical, climatic and other inherited factors and features rather to non-essential. Neither did those authors pay proper attention to the implications of the fact that the built environment which originated with the advent and assertion of Islam on the world scene never existed before, even though the communities that later became instrumental in molding and perpetuating its conspicuous identity, lived where they were for centuries before embracing Islam and possessed the cultures and civilizations of their own. To be sure, studying Islamic built environment by no means can be extricated from the total framework of Islam: its genesis, history, ethos, worldview, doctrines, laws and practices. Any approach by anybody to disconnect Islamic built environment from that which held sway over its conception and formation, would undoubtedly result in failure and, worse yet, may distort the real picture of the subject matter and with it the picture of Islam. For that reason, no sooner had I settled myself in the new academic environment than I decided to embark on a series of research efforts the output of which – it was hoped - will be welcomed by whosoever is interested in the matter, particularly by students of architecture and environmental design in the International Islamic University Malaysia and elsewhere. Within the realm of my capabilities, I targeted some aspects of the most critical areas in the field of Islamic built environment, such as the relationship between man and the natural environment, the significance and character of Islamic architecture, the mosque institution before, during and after the time of the Prophet (pbuh), Islamic housing, mausoleums (shrines) and Islamic urbanism. The outcome of these efforts was a book which consisted of eight standalone articles written over a span of more than a year. Writing the articles was sponsored by the Research Management Center of the International Islamic University Malaysia under the Short-Term Research Grants Scheme, eight papers accounting for eight such grants. Eventually, the book went into its second edition, meaning that it was received rather well by the readers and researchers both inside as well as outside Malaysia. The present form of the book is its third edition. The difference between this and the two earlier editions is that all the papers have been significantly reviewed and modified -- often beyond recognition -- in order to present some new research findings and more mature ideas and thoughts, as well as to fill the glaring gaps which the earlier editions left open. Consequently, the paper on mausoleums (shrines) has been completely done away with, and four new papers on Islamic housing, Islamic aesthetics and Islamic urbanism and its relationship with human development, have been added. The present book thus has eleven chapters, three more than the previous editions. For this edition, too, my profound gratitude is extended to the University’s Research Management Center. My special thanks are also due to the leadership of the Kulliyyah of Architecture and Environmental Design for its unreserved support I always enjoy in the course of my academic engagements. I welcome any constructive and intellectual suggestion concerning the book contents, especially such as pertaining to my methodology, arguments, inferences, and the nature of the collected data and my understanding and interpretation of them.